Various multibody dynamic models for the description of plane Kirchhoff rods - Lang, Holger; Leyendecker, Sigrid; Laube, Hannah (Proceedings of the ECCOMAS Thematic Conference on Multibody Dynamics, 2015)
Three modeling concepts from multibody dynamics (absolute redundant coordinates, minimal relative coordinates and mixed coordinates) are applied to a geometrically exakt discrete viscoelastic Kirchhoff rod model from continuum mechanics. We compare the numerical effort and accuracy, using BDF time integration schemes, established in multibody dynamic
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.ltd.variou
Keywords: Multibody formalism; flexible multibody dynamics; BDF time integration; geometrically exact viscoelastic Kirchhoff rods; absolute & relative coordinates.